Industrially processed v. home-prepared dishes: what economic benefit for the consumer?. Issue 11 (27th August 2020) - Tharrey, Marion; Drogué, Sophie; Privet, Lisa; Perignon, Marlène; Dubois, Christophe; Darmon, Nicole
Abstract: Objective: To cope with the pressure of modern life, consumer demand for convenience foods has increased in the last decades. The current study set out to compare the costs of buying industrially processed dishes and of preparing them at home. Design: Direct purchase costs of industrially processed dishes frequently consumed in France ( n 19) and of the ingredients needed for their home-prepared counterparts ( n 86) were collected from four major food retailers' websites in Montpellier, France. Mean prices and energy density were calculated for four portions. Costs related to energy used by cooking appliances and time spent preparing dishes were further estimated. Setting: Montpellier, France. Participants: Not applicable. Results: Based on the costs of ingredients and energy used for cooking, dishes prepared at home cost less (–0·60 € per four portions, P < 0.001) than industrially processed dishes, but when the cost of time was taken into account, the industrially processed dishes were much cheaper (–5·34 € per four portions, P < 0.001) than their home-prepared counterparts. There was no difference in energy density between industrially processed and home-prepared dishes. Conclusions: Our findings suggest that industrially processed dishes are more profitable to consumers when the cost of time for preparing dishes at home is valued. Given the ever greater demands of everyday life, more account should be taken of the additional cost to consumers of the time they spend preparing meals at home.